A comunicação em fóruns de um curso a distância de formação de professores para uso de TDICS: análise da presença de ensino - Rozenfeld, Cibele Cecílio de Faria [UNESP] (2014)
The importance of the inclusion of digital technology in the classroom has already been pointed out by numerous authors in the educational field and some of them herald that it is through this inclusion that we can achieve transformations in school settings. Based on this assumption, this paper aims to present a distance learning course offered to in service and preservice teachers, focused on the use of technology in foreign language classroom primarily focusing on the role of teacher educators in mediating discussions. For this we sought theoretical support in studies which deal with distance courses (KENSKI, 2008), about virtual environments (ARAÚJO and MARQUESI, 2008), online discussion forums and investigation community and teaching presence (GARRISON, ANDERSON and ARCHER, 2000). Based on the previous theories presented, teacher educator’s messages were analyzed during a distance course offered to teachers in continuing and initial training, identifying marks of teaching presence and pointing to appropriate mediations and/or possible gaps. The results indicate that the teacher must be even more aware of the types of feedback that are provided and of the teaching presence mentioned by Garrison and colleagues (2000, 2001).